Conceptual Basics of Improving Innovative Capacity and its Increase Mechanism - Mambetjanov Qaxramon Gurbandurdievich (Zien Journals, 2023)
This article discusses such issues as innovation, innovative potential and mechanisms for its increase, factors affecting the economic and innovative potential of the country, methods for calculating their level, the relationship of productive forces and relations
Keywords: economic potential; innovation; innovation potential